Faith in the New Testament a study in Biblical theology - Schlatter, Adolf 1852-1938; Longarino, Joseph 1987- (Bellingham, WA Lexham Academic, 2022)
"A classic study now available in English First appearing in 1885, Schlatter's Der Glaube im Neuen Testament (Faith in the New Testament) is a thorough analysis of the concept of faith. Taking into account Old Testament, rabbinic, and key first-century writings, Schlatter provides an exhaustive study on the meaning and implications of faith in the New Testament. It is a philological masterpiece, making its translation into English a great contribution to New Testament theological studies. This fresh translation retains the substance and style of his original work, giving a new audience direct access to Schlatter's work. Schlatter's rigorous thought remains invaluable today"--
Includes indexes
In English, translated from the German, with some phrases in Hebrew and Greek
Keywords: Bible -- Theology; Bible; Faith -- Biblical teaching; Foi - Enseignement biblique; Faith - Biblical teaching; Theology